2013
DOI: 10.1002/ange.201305870
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Molecular Topology of Vinylogous Iminium Ions by Logical Substrate Design: Highly Regio‐ and Stereoselective Aminocatalytic 1,6‐Addition to Linear 2,4‐Dienals

Abstract: Topologie unter Kontrolle: Die Titelreaktion ergibt wertvolle Tetrahydrofuranspirooxindole (siehe Schema; TMS=Trimethylsilyl) und bildet eines von wenigen Beispielen für die 1,6‐Addition an lineare 2,4‐Dienale mit hoher δ‐ und Stereoselektivität. Eine dirigierende Gruppe in β‐Position des Dienals richtet das katalytisch aktive vinyloge Iminiumion‐Intermediat so aus, dass die Reaktion in vorhersehbarer Weise verläuft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Thec omplete regioselectivity of the 1,6-Friedel-Crafts/1,4-oxa-Michael cascade reaction observed is in sharp contrast to what has been found in the other investigations involving linear 2,4-dienals,asthe 1,4-addition is normally favored compared to the 1,6-addition. [5] The remarkable selectivity of the 1,6-addition/1,4-addition cascade in the present development encouraged us to try to elucidate the origin of this selectivity. [3] We have performed calculations,w hich support these results.T o change the reaction course from a1 ,4-addition to as elective 1,6-addition, previous work on regio-and enantioselective 1,6-additions to 2,4-dienals relied on sterically blocking the 4position to suppress the competing 1,4-addition.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thec omplete regioselectivity of the 1,6-Friedel-Crafts/1,4-oxa-Michael cascade reaction observed is in sharp contrast to what has been found in the other investigations involving linear 2,4-dienals,asthe 1,4-addition is normally favored compared to the 1,6-addition. [5] The remarkable selectivity of the 1,6-addition/1,4-addition cascade in the present development encouraged us to try to elucidate the origin of this selectivity. [3] We have performed calculations,w hich support these results.T o change the reaction course from a1 ,4-addition to as elective 1,6-addition, previous work on regio-and enantioselective 1,6-additions to 2,4-dienals relied on sterically blocking the 4position to suppress the competing 1,4-addition.…”
Section: Methodsmentioning
confidence: 84%
“…Theregioselectivity has to be taken into account as both electrophile and nucleophile have multiple reaction sites (Scheme 1). [5] Second, the hydroxyarene can react either through the hydroxy group or aF riedel-Crafts-type reaction in the first step (Scheme 1). Experimental and computational studies have shown that the organocatalytic 1,4-addition is frequently favored over the 1,6-addition.…”
mentioning
confidence: 99%
“…[3] We have performed calculations,w hich support these results.T o change the reaction course from a1 ,4-addition to as elective 1,6-addition, previous work on regio-and enantioselective 1,6-additions to 2,4-dienals relied on sterically blocking the 4-position to suppress the competing 1,4-addition. [5] The remarkable selectivity of the 1,6-addition/1,4-addition cascade in the present development encouraged us to try to elucidate the origin of this selectivity. Scheme 1s hows the four possible products (I-IV)o ft he cascade reaction, but only I is observed.…”
Section: Angewandte Zuschriftenmentioning
confidence: 96%
“…[3] Except for one single example [4] in which unbiased aliphatic 2,4-dienals were used, all previous studies of regio-and enantioselective 1,6-additions to 2,4-dienals have relied on sterically blocking the 4-position to suppress the competing 1,4-addition. [5] Second, the hydroxyarene can react either through the hydroxy group or aF riedel-Crafts-type reaction in the first step (Scheme 1). Furthermore,the control of stereoselectivity is another equally important challenge which must be addressed as the initial stereocenter is formed at the 6-position of the aldehyde,six bonds away from the stereocenter of the catalyst.…”
mentioning
confidence: 99%
“…8 For example, N-methylwelwitindolinone D (A) and HepG2 (B) are used as an anticancer agent and growth inhibitor, respectively, 9 compound C shows antifungal activity, 10 and compounds D−F display antitobacco mosaic virus and cytotoxic activities (Scheme 1a). 11 The construction of such skeletons has attracted significant attention from chemists, including Lewis acid-catalyzed [3 + 2] cycloaddition of vinyl silanes with isatins, 12 aminocatalytic 1,6-addition of 3hydroxy-2-oxindoles to linear 2,4-dienals, 13 three-component reactions of isocyanides, substituted allenoates, and isatins, 14 palladium-catalyzed asymmetric [3 + 2] cycloaddition of vinyl cyclopropanes and isatins, 15 phosphine-catalyzed [3 + 2] cycloaddition of ynones and isatins, 16 and acid-catalyzed intramolecualr cyclization of 3-allyl-3-hydroxy-2-oxindoles. 17 In 2019, Aksenov, Rubin, and co-workers reoprted the [4 + 1] cycloadducts of indoles and nitrostyrenes.…”
mentioning
confidence: 99%